ALK-rearranged lung adenocarcinoma transforming to mucoepidermoid carcinoma in a 45-year-old female: a case report - Liu, Yachen; Liu, Xi; Ma, Hongmeng; Li, Wenxin (AME Case Reports, 2026)
Background: Pulmonary mucoepidermoid carcinoma (PMEC) accounts for less than 1% of pulmonary malignancies and is predominantly primary, exhibiting distinct clinical manifestations and treatment responses compared to lung adenocarcinoma (LUAD). Although the incidence of histological transformation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) following tyrosine kinase inhibitor (TKI) therapy is approximately 3–14%, transformation from LUAD to PMEC is an extremely rare event. Currently, there is a lack of unified understanding and diagnostic/therapeutic guidelines concerning its mechanism, clinical features, treatment strategies, and prognosis. This article reports a case of HT from LUAD to PMEC following anaplastic lymphoma kinase (ALK)-TKI therapy, aiming to enhance clinicians’ awareness of this rare condition and provide preliminary reference for the diagnosis and management of similar cases.Case Description: This report describes a 45-year-old female patient who was admitted to the hospital with a chief complaint of “persistent cough, sputum production, and dyspnea for 2 years, accompanied by chest tightness for 1 week”. She was diagnosed with ALK exon 20 mutation-positive left LUAD (cT1N1M1, stage IV). After 28 months of first-line ALK-TKI alectinib therapy, the patient experienced disease progression. Repeated pathological biopsy confirmed a transition from LUAD to PMEC, with persistent ALK mutation. Subsequent treatment included lorlatinib and third-line chemotherapy (pemetrexed/carboplatin regimen for four cycles), achieving acceptable disease control. The progression-free survival (PFS1) prior to transformation was 8 months, and the patient is currently receiving palliative care.Conclusions: Tumors that undergo LUAD-to-PMEC transformation after ALK-TKI therapy exhibit persistently low levels of ALK fusion and characteristic immunohistochemical alterations [deletion of thyroid transcription factor-1 (TTF-1)/Napsin A, upregulated expression of CK5/6/P40], along with inherent resistance to ALK-TKIs. When heterogeneous resistance emerges during TKI therapy, prompt repeat biopsy with concurrent pathological and next-generation sequencing (NGS) testing is recommended. If confirmed, immediate transition to phenotype-specific therapy should be initiated. Although this is a single-case observation requiring validation in larger cohorts, these findings provide preliminary guidance for clinical identification and management of such rare transformations.